NLRP3 inflammasome mediates 2, 5-hexanedione-induced neurotoxicity through regulation of macrophage infiltration in rats. (1st October 2020) - Huang, Ruixue; Hou, Liyan; Ruan, Zhengzheng; Zhang, Dongdong; Sun, Wei; Wang, Qingshan
Abstract: Currently, whether nod-like receptor family pyrin domain-containing 3 (NLRP3) inflammasome activation contributes to neuropathy induced by 2, 5-Hexanedione (HD), the toxic metabolite of n -hexane, remains unknown. In this study, we found that HD intoxication elevated NLRP3 expression, caspase-1 activation and interleukin-1β production in sciatic nerve of rats, indicating activation of NLRP3 inflammasome. The increased cleavage of gasdermin D (GSDMD) protein, an important mediator of pyroptosis, and axon degeneration were also observed in sciatic nerves of HD-intoxicated rats. Interestingly, glybenclamide, a widely used inhibitor of NLRP3 inflammasome, significantly reduced NLRP3 inflammasome activation, which was associated with decreased GSDMD cleavage and axon degeneration as well as improved motor performance of HD-intoxicated rats. Subsequently, we found that inhibition of NLRP3 inflammasome by glybenclamide attenuated macrophage infiltration, activation and M1 polarization in sciatic nerves of HD-intoxicated rats. Furthermore, decreased malondialdehyde (MDA) contents and increased glutathione (GSH) level and total anti-oxidative capacity were also observed in sciatic nerves of rats treated with combined glybenclamide and HD compared with HD alone group. Altogether, our findings suggest that NLRP3 inflammasome activation contributes to HD-induced neurotoxicity by enhancing macrophage infiltration and activation as well as oxidative stress, providing a novel mechanism of neuropathy induced by this neurotoxicant. Highlights: HD induces NLRP3 inflammasome activation in sciatic nerve of rats. NLRP3 inflammasome inhibitor glybenclamide protects against HD-induced toxicity. Glybenclamide inhibits HD-induced macrophage infiltration and M1 activation.